Who said red? - Serfozo, Mary.; Narahashi, Keiko (New York : M.K. McElderry Books, 1988)
A dialogue between two speakers, one of whom must keep insisting on an interest in the color red, introduces that hue as well as green, blue, yellow, and others.
2.0
K-3
K-3
Wilson's Children
Elem. School Library Collection
School Library Journal starred
Keywords: Color -- Fiction; Stories in rhyme; Color -- Fiction